Buffeting analysis of cable-stayed bridges during their erection. - Huang, Zhong Ying. (University of Ottawa (Canada), 1995)
Buffeting response of cable-stayed bridges at their erection stage under yawed wind has attracted engineering attention through wind tunnel observations and studies. Cable-stayed bridges are particularly vulnerable to dynamic wind effects during their construction stages due to the lack of overall structural stiffness. The most critical stage is just before the bridge main span is closed. At this time, a cable-stayed bridge resembles a long cantilever structure supported by cables, and particularly, the fundamental frequency horizontal modes of oscillation may be very low. During this stage, the cable-stayed ridge is more responsive to wind action both in lateral and vertical bending. For this reason, the prediction of wind-induced bridge response becomes more important when directional variation of wind is considered. However, only a few theoretical approaches have been proposed, applicable only in extremely simplified cases. This thesis deals with the prediction of buffeting response of cable-stayed bridges under yawed winds using the modified buffeting analysis. The modified buffeting analysis was originally developed by Kimura (1991) and was restricted to vertical bending response. The comparison with experimental data was also conducted for extremely simplified flat plate models. In this thesis, the modified buffeting approach is not only applied to actual cable-stayed bridge models but also the calculation of the lateral bending oscillation has been attempted. Further, the calculated results are compared with the experimental data obtained from the wind tunnel tests of the aeroelastic cable-stayed bridge models; the Normandy Bridge and the Kao Ping Hsi Bridge.
Keywords: Engineering, Civil.